Svistella cangshanensis Ma & Tao, sp. nov., a new species of Trigonidiinae (Orthoptera: Trigonidiidae) from China - Tao, Li-Long; Yuan, Wei; Ma, Li-Bin (Zootaxa, 2025)
Svistella Gorochov, 1987 is a genus of sword-tailed crickets whose males bear long tegmina and long oval-shaped mirror. There are 11 species of Svistella recorded worldwide, and 10 are distributed in China. In this article, we describe a new species of Svistella from Yunnan Province (Svistella cangshanensis Ma & Tao sp. nov.). The new species is similar to Svistella wuyong He, 2021, however, the pronotum of S. wuyong is reddish-brown and there are black spots on both sides of the end of the posterior femora, the pronotum of S. cangshanensis is yellowish-brown and there are black spots in the center and both sides of the pronotum. Moreover, there are also differences in genitalia. In S. wuyong, the end of the lateral lobe of the epiphallus becomes narrow, sharp and almost straight; while in S. cangshanensis, this part becomes narrow and sharp with curvature and the inner lobe has denticles. In this article, we describe and illustrate the new species and provide keys for the Chinese Svistella species.